2016
DOI: 10.1007/s00726-016-2296-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the interaction between transglutaminase 2 and fibronectin

Abstract: In the extracellular environment, the enzyme transglutaminase 2 (TG2) is involved in cell-matrix interactions through association with the extracellular matrix protein, fibronectin (FN). The 45 kDa gelatin-binding domain of FN (45FN) is responsible for the binding to TG2. Previous studies have demonstrated that the FN-binding site of TG2 is located in the N-terminal domain of the enzyme although with conflicting results regarding the specific residues involved. Here we have mapped the FN interaction site of hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 47 publications
4
40
3
Order By: Relevance
“…Previous studies identified the β hairpin loop as the FN-binding region (amino acids 88–106) (7). However, more recent analyses using hydrogen/deuterium exchange and mass spectrometry point to residues K30, R116, and H134 in the N-terminus as being critical to forming a complex with the 42 kDa gelatin-binding domain of FN (8). On the surface of cells, the complex between TG2 and FN is further supported and stabilized by direct interactions of both proteins with integrins, the major receptors involved in cellular adhesion to the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies identified the β hairpin loop as the FN-binding region (amino acids 88–106) (7). However, more recent analyses using hydrogen/deuterium exchange and mass spectrometry point to residues K30, R116, and H134 in the N-terminus as being critical to forming a complex with the 42 kDa gelatin-binding domain of FN (8). On the surface of cells, the complex between TG2 and FN is further supported and stabilized by direct interactions of both proteins with integrins, the major receptors involved in cellular adhesion to the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…We also tested a chimeric variant of TG2 where the entire TG2 N‐terminal domain is exchanged with the corresponding amino acid residues of TG3 . This protein no longer binds FN and is not recognized by the celiac mAbs targeting any of the four major epitopes . Importantly, both these proteins showed comparable binding to the small intestinal tissue ECM as observed for full‐length WT TG2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The above models clearly point to the TG2 interaction region reported by Cardoso et al (32), and we therefore ran a second set of simulations, with Haddock (https://haddock.science.uu.nl/) (49), driven by the experimental information. For the docking simulations with Haddock, the TG2 open conformation was used vs. the same fibronectin fragment used above (residues 516-602, PDB ID: 3GXE).…”
Section: Docking Simulationsmentioning
confidence: 96%
“…From this set of results, we filtered out all the solutions that did not match the previously reported (15,32,47) and current experimental data. Toward this goal, we analyzed the interface of the models and selected for further analyses only models featuring more than 50 interatomic contacts (using a cutoff of 5Å) between the N-terminal region of TG2 (residues 1-230) and the FN I 8 module.…”
Section: Docking Simulationsmentioning
confidence: 99%
See 1 more Smart Citation